Dynamics in Pulmonary Edema and Impaired Vascular Permeability in Severe Concomitant Injury: - V. V. Moroz; A. M. Golubev; D. V. Lysenko (Общая реаниматология, 2006)
Early changes in the content of extravascular fluid in the lung and in the permeability of pulmonary vessels were studied in patients experiencing a severe concomitant injury with acute massive blood loss. It has been found that monitoring of the parameters of extravascular liquid in the lung and the permeability of pulmonary vessels by a PiCCOplus (Pulsion Medical Systems, Germany) invasive monitor in the early posttraumatic period enables the early stages of pulmonary edema and pulmonary vascular permeability to be verified and the risk of acute lung lesion to be assessed.